GIS BASED SOIL SITE SUITABILITY ANALYSIS FOR POTATO - A CASE STUDY IN LOWER INDOGANGETIC ALLUVIAL PLAIN - Dharumarajan, S; Singh, S K (Potato Journal, 2015)
To identify the best suitable land parcels for potato cultivation, soil site suitability evaluation was carried out using GIS techniques. The study was carried out in Puinan village clusters of Chinchura-Mogra block of Hooghly district. Resourcesat-2 LISS IV data in conjugation with cadastral map was used to identify the different soil mapping units of the area. Land suitability assessment was carried out by using the parametric methodology in GIS environment. The results showed that 9.8% of area is highly suitable and 15.7% and 27.9% of study area are moderately and marginally suitable respectively. Due to heavy texture, drainage and other soil related problems, 46.6% of study area is not suitable for potato cultivation. These results would be useful to the local stakeholders for increasing their economic production by identifying highly and moderately suitable land parcels for cultivation.